Competence and collectivity: The discourse of Angela Merkel's media communications during the first wave of the pandemic. (August 2021) - Jaworska, Sylvia
Abstract: Understanding leadership as a discursive performance, this study explores televised speeches and press briefings on Covid-19 given by the German chancellor Angela Merkel in March and April 2020. Merkel's televised communications deserve special attention for at least two reasons; first, Merkel was hailed as one of the few national leaders who successfully led through the first wave of the pandemic. Secondly, her communications were praised as examples of successful persuasive efforts. Using a corpus-assisted approach, this study identifies the frequent lexico-grammatical devices that she employed to do her 'convincing' work. The study then compares the identified features against her communicative style in speeches delivered in pre-pandemic times. The comparative insights show that in the limited mediatised time, Merkel chose a specific set of lexico-grammatical devices including certain pronouns, modal verbs, time deictics and logical connectors that highlighted the interpersonal dimension of her communications, urgency of the situation and logical cause-effect argumentation. While these devices were not entirely new in Merkel's public statements, they were used with much higher frequency in her Covid-19 speeches signalling a discursive change in her communicative style during the evolving health crisis. The study provides support for the notion of (effective) leadership as a discursive and situated activity; an effective leader will select certain language devices from the available pool of resources that are appropriate to the context of the situation (here the Covid-19 pandemic) and its aims (persuading citizens to adhere to preventative measures). The paper finishes with an assessment of Merkel's mediatised discourse during the first two months of the pandemic against her overall communicative style. It argues that the successfulness of her Covid-19 televised performances depended not just on the use of specific discursive devices but also on the contrast that they created with her usual impersonal approach.